Effects of high temperature during grain filling on physicochemical properties of waxy maize starch - Da-lei LU; Huan YANG; Xin SHEN; Wei-ping LU (Journal of Integrative Agriculture, 2016)
Abstract: Understanding the waxy maize starch physicochemical properties response to heat stress during grain filling could improve starch quality. The effects of heat stress during early (1–15 days after pollination, DAP) and late (16–30 DAP) grain filling stages on the starch physicochemical properties of four waxy maize varieties were evaluated. Crystallinity only increased in Suyunuo 5 after exposure to high temperature at late grain filling stage. The effects of heat stress on digestibility and swelling power were dependent on varieties and stages. Generally, swelling power was increased by heat stress at early grain development stage and digestibility was increased by high temperature at late grain filling stage, respectively. The results of correlation analysis indicated the starch with large granule size could swell well and easy digest. Peak, trough, final, and breakdown viscosities in response to heat stress were dependent on stages and varieties. In general, peak, trough and final viscosities were decreased and increased by heat stress at early grain formation and late grain filling stages, respectively; whereas the breakdown and setback viscosities were similar among the three treatments. Heat stress increased the gelatinization temperatures and retrogradation percentage. Gelatinization range decreased under heat stress at 1–15 DAP but remained constant under heat stress at 16–30 DAP in all varieties. The starch exposed to high temperature at 16–30 DAP presented higher digestibility and peak viscosity and lower retrogradation percentage than those at 1–15 DAP. Therefore, heat stress at early grain formation stage severely affects the physicochemical properties of starch.